An Emotion-Enriched Context Influences the Effect of Action Observation on Cortical Excitability - Lagravinese, Giovanna; Bisio, Ambra; De Ferrari, Alessia Raffo; Pelosin, Elisa; Ruggeri, Piero; Bove, Marco; Avanzino, Laura (Frontiers in Human Neuroscience, 2017)
Observing other people in action activates the “mirror neuron system” that serves for action comprehension and prediction. Recent evidence suggests that this function requires a high level codification triggered not only by components of motor behavior, but also by the environment where the action is embedded. An overlooked component of action perceiving is the one related to the emotional information provided by the context where the observed action takes place. Indeed, whether valence and arousal associated to an emotion might exert an influence on motor system activation during action observation has not been assessed so far. Here, cortico-spinal excitability of the left motor cortex was recorded in three groups of subjects. In the first condition, motor evoked potential (MEPs) were recorded from a muscle involved in the grasping movement (i.e. abductor pollicis brevis, APB) while participants were watching the same reach-to-grasp movement embedded in contexts with negative emotional valence, but different levels of arousal: sadness (low arousal), and disgust (high arousal) (“Context plus Movement-APB” condition). In the second condition, MEPs were recorded from APB muscle while participants were observing static images representing the contexts in which the movement observed by participants in “Context plus Movement-APB” condition took place (“Context Only-APB” condition). Finally, in the third condition, MEPS were recorded from a muscle not involved in the grasping action, i.e. abductor digiti minimi, ADM, while participants were watching the same videos shown during the “Context plus Movement-APB” condition (“Context plus Movement-ADM” condition). Results showed a greater increase of cortical excitability only during the observation of the hand moving in the context eliciting disgust, and these changes were specific for the muscle involved in the observed action. Our findings show that the emotional context in which a movement occurs modulates motor resonance and that the combination of negative valence/high arousal drives the greater response in the observer’s mirror neuron system in a strictly muscle specific fashion.